Isolation and identification of microbes from various fruit juices made and sold for immediate consumption at home and in the market of Dhaka city - Mortuza, Tasnim (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirement for the degree of B.Sc in Microbiology, 2016.